2021
DOI: 10.1021/acs.energyfuels.1c01007
|View full text |Cite
|
Sign up to set email alerts
|

High Selectivity CO2 Capture from Biogas by Hydration Separation Based on the Kinetic Difference in the Presence of 1,1-Dichloro-1-fluoroethane

Abstract: The separation of a gas mixture by hydrate technology is considered one of the most promising new separation technologies. Previous studies on biogas purified by hydrate separation had high energy consumption because of low separation efficiency. In this paper, we used 1,1-dichloro-1-fluoroethane (HCFC-141b) as an additive to capture CO2 from a mixture gas of 67.00 mol % CH4 and 33.00 mol % CO2, which not only reduced the hydrate formation pressure but also enhanced the difference of methane and carbon dioxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Babu et al calculated the energy consumption of the hydrate-based seawater desalination process and found that the refrigeration process had the largest energy consumption. Wang et al calculated the energy consumption of the biogas separation process by the hydrate method and obtained a unit energy consumption of 0.3530 kWh/kg CH 4 . Furthermore, gas hydrates have the ability to be stored at specific temperatures under atmospheric pressure, known as the self-preservation effect. Using the self-preservation effect of hydrates, CO 2 can be stored as hydrates easily. , …”
Section: Introductionmentioning
confidence: 99%
“…Babu et al calculated the energy consumption of the hydrate-based seawater desalination process and found that the refrigeration process had the largest energy consumption. Wang et al calculated the energy consumption of the biogas separation process by the hydrate method and obtained a unit energy consumption of 0.3530 kWh/kg CH 4 . Furthermore, gas hydrates have the ability to be stored at specific temperatures under atmospheric pressure, known as the self-preservation effect. Using the self-preservation effect of hydrates, CO 2 can be stored as hydrates easily. , …”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al studied the effect of the gas–liquid ratio on N 2 –CH 4 separation efficiency under the addition of tetrahydrofuran, indicating that a low gas–liquid ratio would increase the separation of CH 4 but reduce the hydrate formation rate. Wang et al investigated the influence of HCFC-141b concentration, feed gas pressure, and the initial gas/liquid volume ratio on separation efficiency and the kinetics of hydrate formation at 284.1 K. With the decrease of the initial gas/liquid volume ratio and HCFC-141b concentration, the CH 4 concentration in the residual gas phase increased, but the CH 4 recovery ratio decreased due to more formation of the CH 4 hydrate. Cheng et al studied the influence of the pressure driving force (4, 6, 8 MPa) and gas–liquid ratio on the formation and separation efficiency of the CO 2 /CH 4 binary mixed hydrate at 275.15 K in the presence of 500 ppm of SDS.…”
Section: Introductionmentioning
confidence: 99%
“…Since carbonated frozen dessert (CO 2 hydrate dessert) has a greater CO 2 concentration than carbonated beverages, it could be applied to carbonate the dessert or ice cream . Also, it has been suggested that CO 2 , , SF 6 , cyclopentane, and refrigerant gases (HCFC-141b, , HFC-134a) have proper potential for effluent concentration and desalination targets. This process was simply designed based on crystal formation in a saltwater solution followed by hydrate-saline water separation and then hydrate dissociation.…”
Section: Introductionmentioning
confidence: 99%